Purchase Decisions: The Role of Content and Augmented Reality Mediated by Purchase Interest - Windarko, Windarko (Dinasti Publisher, 2025)
This study aims to analyze the influence of Content Marketing and Augmented Reality (AR) on Purchase Decision of beauty products on marketplace applications , with Purchase Intention as a mediator variable . The emergence of digital marketing technology such as Virtual Try-On features on platforms like Shopee and TikTok Shop has been reshaped consumer behavior in making purchase decisions . This research employs a quantitative method using Structural Equation Modeling (SEM) based on Partial Least Squares , analyzed through SmartPLS 4.0. The results show that Augmented Reality has a significant and positive effect on Purchase Intention and indirectly influences Purchase Decision through Purchase Intention . On the others hand , Content Marketing does not mean affect Purchase Intention , but it directly affects Purchase Decision . These findings suggest that immersive experiences enabled by AR are more effective in stimulating consumers ' intention to buy than conventional marketing content.